Positive Politeness Strategies in Main Character “Moana II” Movie Utterances - Dwi Juliatiningrum, Amanda (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2025)
This study analysis discusses how often positive politeness appears in the main character's dialogue in the film "Moana 2", what are the functions of positive politeness strategies used in the film "Moana 2" and what are the factors that cause positive politeness strategies to be used in the film "Moana 2". The purpose of this study was to determine how often, what the types, factor and functions of politeness strategies used by the main character in the film "Moana 2", to obtain the types of dominant politeness strategies produced by the main character in the film "Moana 2" and to describe the context of politeness strategies used by the main character in the film "Moana 2". The data of this study are the dialogues of the main characters in the film "Moana 2". This study was conducted using a descriptive qualitative design and only focused and limited to the main character. . In this analysis, positive politeness itself was found to have 5 types, namely notice, exaggrate, use in-group identity markers, avoid disagreement and use friendly and respectful language. The findings of this study are 68 positive politeness strategies. The most dominant politeness strategy spoken by the main character in the film "Moana 2" is use friendly and respectful language. This positive politeness strategy occurs because the main character speaks with politeness and politeness that is inherent as their culture and is in a royal environment.